2017
DOI: 10.1108/bfj-11-2016-0532
|View full text |Cite
|
Sign up to set email alerts
|

Study effect of natural extracts on the antioxidant activity in pork balls

Abstract: Purpose The purpose of this paper is to investigate the potential of fruit waste materials from fruit industry as sources of powerful natural antioxidants. Design/methodology/approach The peels of mango, rambutan, and santol were extracted and analyzed for their antioxidant activity. Pork ball samples were prepared and treated with different natural extracts at various concentrations, namely 0.05, 0.10, 0.15, and 0.20% (v/w), compared with the control (no natural extract), and then stored at 4°C. The samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Several scientific works stand out with a focus on the antioxidant activity of the bioactive compounds present in different parts of the mango. One of these papers reported that, when using phenolic extracts of mango peels (20% v/p) in the preservation of pork balls, high efficacy of polyphenols antioxidant activity against lipids oxidation was found [165]. In the same sense, mango pulp extracts improved the oxidative stability of soybean oil, resembling the protection observed when using synthetic antioxidants such as BHT and TBHQ [166].…”
Section: Human Foodmentioning
confidence: 93%
“…Several scientific works stand out with a focus on the antioxidant activity of the bioactive compounds present in different parts of the mango. One of these papers reported that, when using phenolic extracts of mango peels (20% v/p) in the preservation of pork balls, high efficacy of polyphenols antioxidant activity against lipids oxidation was found [165]. In the same sense, mango pulp extracts improved the oxidative stability of soybean oil, resembling the protection observed when using synthetic antioxidants such as BHT and TBHQ [166].…”
Section: Human Foodmentioning
confidence: 93%